BIOLOGY, ECOLOGY AND TROPHIC ECOLOGY OF COMMON KILKA CLUPEONELLA DELICATULA CASPIA SVETOV - M. M. Elizarenko; A. F. Sokolsky; G. M. Abdurakhmanov (Юг России: экология, развитие, 2014)
Long-term materials on ecology ordinary sprat are resulted.